"Thoughts of a Social Work Distance Education Teacher." - Jennings, Joanne (1997)
Keywords: dept.swk; faculty_collection; sabbatical_report

Normalizing acute care: A day hospital/crisis residence alternative to inpatient hospitalization - Rakfeldt, J.; Tebes, J.K.; Steiner, J.; Walker, P.L.; Davidson, L.; Sledge, W.H. (Journal of Nervous and Mental Disease, 1997)
Normalization is the use of culturally valued means to enable people with disabilities to live culturally valued lives. In this article, the authors describe an effort to bring normalization practices to acute psychiatric care. They describe a day hospital/crisis respite diversion program that serves as an alternative to acute inpatient hospitalization and sketch the research project that fostered it. The authors argue that a day hospital/crisis respite provides effective clinical care comparable to inpatient hospitalization but achieves greater potential for recovery through a normalizing philosophy and practice. An implication of this finding is that such programs based on the principle of normalization may be both cost effective as well as more empowering for patients.
Keywords: Acute Disease; Adult; Bipolar Disorder; Community Mental Health Centers; Cost-Benefit Analysis; Crisis Intervention; Day Care; Female; Group Homes; Health Care Costs; Health Services Research; Hospitalization; Humans; Mental Disorders; Psychotic Disorders; adult; article; case report; crisis intervention; day hospital; dept.swk; female; human

Program design and planning strategies in the delivery of culturally competent health and mental health prevention and treatment services to latino communities - Colon, Edgar (Journal of Multicultural Social Work, 1997)
It is important that the delivery of health and mental health prevention and treatment services within Latino communities be culturally sensitive. This article outlines several ways in which agencies can develop programs that can meet the needs of Latino communities. The most important aspect of the provision of health prevention and treatment services is that the organization integrates itself into the community through outreach, recruitment, and inclusion in decision-making. In addition, the organization needs to be structured so communication and participation from the community and health professionals are open and mixed. Otherwise, the likelihood of success of the provision of services in the community will be diminished. © 1996 Taylor & Francis Group, LLC.
Keywords: dept.swk